1983
DOI: 10.1111/j.1365-2133.1983.tb03544.x
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal Langerhans cells induce cellular immune response to trichophytin in dermatophytosis

Abstract: Human epidermal cell suspensions were prepared from patients sensitized to trichophytin. The cells were 75% to 95% viable, and contained 2% to 6% Langerhans cells as judged by immunofluorescence staining with an anti-DR antiserum. T lymphocytes from the same patients were co-cultured with trichophytin, with or without epidermal cells or macrophages. Proliferative T-cell response to trichophytin was obtained in cultures containing epidermal cells or macrophages. Pretreatment of the epidermal cells with anti-DR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…Numerous studies have suggested that LC represent a critical antimicrobial barrier in the skin against viral, bacterial, parasitic and fungal infections [8,11,13,26]. The present findings corroborate the finding of Nagao and Inaba [18] that LC are involved in the response of the skin to infection with VV.…”
supporting
confidence: 95%
“…Numerous studies have suggested that LC represent a critical antimicrobial barrier in the skin against viral, bacterial, parasitic and fungal infections [8,11,13,26]. The present findings corroborate the finding of Nagao and Inaba [18] that LC are involved in the response of the skin to infection with VV.…”
supporting
confidence: 95%
“…For the develop ment of allergic contact dermatitis, fungal antigens in the epidermis must be taken up and presented to T lympho cytes by Langerhans cells to induce antigen-specific responses. In vitro studies by Braathen and Kaaman [31] demonstrated that Langerhans cells are able to present dermatophyte antigens to T lymphocytes.…”
Section: Dermatophytosis As Contact Dermatitismentioning
confidence: 99%
“…Local immunologic factors have been considered to be involved but until now the theoretical background has been poorly understood. Langerhans' cells are thought to take part in the presentation of the antigen to the immune system and the occurance of Langerhans' cells in the palms and soles are reported to be reduced as compared to the skin of other parts of the body (2). However other local factors of resistence might also be of interest as shown by cases of keratoderma hereditaria where the stratum corneum of palms and soles is hypertrophic.…”
Section: Discussionmentioning
confidence: 99%